2018
DOI: 10.1093/femspd/fty013
|View full text |Cite
|
Sign up to set email alerts
|

Human lung epithelial cells support human metapneumovirus persistence by overcoming apoptosis

Abstract: Human metapneumovirus (hMPV) has been identified as a major cause of lower respiratory tract infection in children. Epidemiological and molecular evidence has highlighted an association between severe childhood respiratory viral infection and chronic lung diseases, such as asthma and chronic obstructive pulmonary disease. Currently, animal models have demonstrated the ability of hMPV to persist in vivo suggesting a role of the virus in asthma development in children. However, mechanisms involved in hMPV persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In general, viruses may be able to persist by interfering with the induction of apoptosis. Supporting that, chronic hMPV infection in AECs increased expression of the anti-apoptotic Bcl-2 protein, which overthrows the apoptotic program [89].…”
Section: Airway Epithelial Cells (Aecs)mentioning
confidence: 75%
See 2 more Smart Citations
“…In general, viruses may be able to persist by interfering with the induction of apoptosis. Supporting that, chronic hMPV infection in AECs increased expression of the anti-apoptotic Bcl-2 protein, which overthrows the apoptotic program [89].…”
Section: Airway Epithelial Cells (Aecs)mentioning
confidence: 75%
“…It is important to note that hMPV persistence has only been described in some mouse studies [54,[91][92][93] and a few immunocompromised patients of which some had no symptoms [42,43,94]. Additionally, hMPV persistence has been described in vitro in A549 cells by Marsico et al [89]. This study showed that at 14 dpi, the hMPV-infected cells were still metabolically active which could represent the beginning of coexistence between AECs and hMPV and thus transition from acute to persistent infections.…”
Section: Airway Epithelial Cells (Aecs)mentioning
confidence: 90%
See 1 more Smart Citation
“…Typically, death of infected host cells implies a reduction in viral replication and an increase in the capacity of antigen presentation by immune cells. A study performed by Marsico et al described in human alveolar epithelial A549 cells that hMPV is able to persist through the inhibition of the apoptosis machinery ( 24 ). This effect was associated with an increase in the expression of Bcl-2, an antiapoptotic factor from the Bcl-2 family, in the surface of hMPV-infected cells after 14 days of infection.…”
Section: Persistence Of Hmpv In Epithelial Cellsmentioning
confidence: 99%
“…This effect was associated with an increase in the expression of Bcl-2, an antiapoptotic factor from the Bcl-2 family, in the surface of hMPV-infected cells after 14 days of infection. In addition, the authors postulated a direct correlation between cellular survival and viral replication, suggesting that hMPV starts its infective cycle with a strong peak of replication and a significant increase in cellular apoptosis, followed by a decrease in viral infective rates, promoting a slow cellular proliferation, overcoming apoptosis and inducing cell cycle arrest in G2/M ( 24 ). On the other hand, hRSV-infection has been associated with an early induction of Mcl-1 -another antiapoptotic factor that belongs to the Bcl-2 family- along with more antiapoptotic factors (Bcl-W, Bcl-xL) and pro-apoptotic factors (Bid, Bax, Bak), which all could be mediated by the NF-κB pathway ( 25 ), suggesting that hMPV could also be using others factor from the Bcl-2 family.…”
Section: Persistence Of Hmpv In Epithelial Cellsmentioning
confidence: 99%